ANALISIS SEMIOTIKA TERHADAP IKLAN SPRITE EDISI MITOS VS KENYATAAN DI TELEVISI - Witanti Prihatiningsih (Universitas Bunda Mulia, 2016)
This research analyzes the Myth Vs Reality edition of Sprite advertisement. The company wants to offer the freshness of the product with the advertisement. This research applies the semiotic perspective from Roland Barthes to analyze connotation, denotation, myth and ideology to find the message behind the advertisement. This research uses qualitative approach and semiotic analysis method. The primary data is Myth Vs Reality edition of Sprite advertisement record. The secondary data is literary review and other information. This researcher analyzes the advertisement with the semiotic model from Roland Barthes. This researcher analyzes all communication icons and cinematographic aspects in the advertisement. Finally, researcher concludes that the advertisement urges people to think logically. It urges people to understand that a drink cannot make them suddenly rich or get the ideal lover without doing nothings. However, a drink makes the body fresh and Sprite is a lime-flavored soda that can make the body fresh.Keywords: Advertisement, Semiotics, Roland Barthes